Pharmacokinetics and disposition characteristics of recombinant decorin after intravenous injection into mice - Masuda, Hideo; Takakura, Yoshinobu; Hashida, Mitsuru (Biochimica et biophysica acta, 1999)
The pharmacokinetics and disposition characteristics of recombinant decorin after intravenous administration were investigated in mice. Following bolus injection of 111In-labeled decorin at doses of 0.02 and 0.1 mg/kg, radioactivity rapidly disappeared from the circulation and approximately 70% of the dose accumulated in liver within 10 min. 111In-labeled decorin was preferentially localized in hepatic nonparenchymal cells. At a higher dose of 1 mg/kg, clearance from the circulation and hepatic uptake of [ 111In]decorin were slower than at lower doses. Both the accumulation in other tissues and urinary excretion of [ 111In]decorin were 5% or less. Pharmacokinetic analysis demonstrated that hepatic uptake clearance was large and accounted almost completely for total body clearance; in addition the clearance values decreased as the dose increased, suggesting that the hepatic uptake of decorin is mediated by a specific mechanism which becomes saturated at higher doses. In competitive inhibition experiments, hepatic uptake of 111In-labeled decorin was partially inhibited (about 20–30%) by several sulfated glycans such as glycosaminoglycans and dextran sulfate and by mannosylated bovine serum albumin (BSA), mannan and mannose to a lesser extent (about 10%). On the other hand, polyinosinic acid, polycytidylic acid and succinylated BSA were ineffective, suggesting that the scavenger receptor for polyanions in the liver is not involved in the hepatic uptake of decorin. A basic protein, protamine, and a ligand of the apoE receptor, lactoferrin, also had no effect. Taken together, the present results have demonstrated that recombinant decorin is rapidly eliminated from the blood circulation through extensive uptake by the liver, primarily by the nonparenchymal cells, following systemic administration. The sugar structure and mannose residue in decorin have also been suggested to play an important role in the hepatic uptake of decorin. These findings provide useful information for the development of decorin as a therapeutic agent.